2012
DOI: 10.1007/s10800-012-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lithium difluoro(oxalate)borate (LiDFOB) additive on the performance of high-voltage lithium-ion batteries

Abstract: Lithium difluoro(oxalato)borate (LiDFOB) was investigated as an electrolyte additive for high-voltage lithium-ion batteries in order to decrease the decomposition of the electrolyte. As a typical high-voltage cathode material, LiCoPO 4 was tested in the LiDFOB-containing electrolyte, exhibiting higher reversible charge/discharge capacity and better cyclic stability. The effect of LiDFOB on the formation of a stable interphase film was investigated through cyclic voltammetry and X-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 54 publications
2
53
0
2
Order By: Relevance
“…For the pristine PEO-LiDFOB electrolyte, the B1s peak at 192.0 eV, as well as the B1s peak at 193.4 eV and F1s peak at 686.1 eV, corresponded to B-O and B-F of LiDFOB, respectively. 30 After 20 cycles charging and discharging, the relative intensity of B-O peak increased remarkably, but the F1s (B-F) peak changed barely. Xu et al have reported that the ring opening process could reduce the symmetry and the coordinated number of B center and make the B1s peak shift to a lower binding energy.…”
Section: Vs Li/limentioning
confidence: 89%
See 1 more Smart Citation
“…For the pristine PEO-LiDFOB electrolyte, the B1s peak at 192.0 eV, as well as the B1s peak at 193.4 eV and F1s peak at 686.1 eV, corresponded to B-O and B-F of LiDFOB, respectively. 30 After 20 cycles charging and discharging, the relative intensity of B-O peak increased remarkably, but the F1s (B-F) peak changed barely. Xu et al have reported that the ring opening process could reduce the symmetry and the coordinated number of B center and make the B1s peak shift to a lower binding energy.…”
Section: Vs Li/limentioning
confidence: 89%
“…Moreover, a new B1s peak emerged at 192.8 eV, which was associated with the decomposition products of LiD-FOB, such as Li x BO y F z species. [30][31][32][33] Compared with the XPS results of PEO electrolyte from the LiCoO 2 /PEO-LiDFOB/Li cell, these new species may be resulted from the interface reaction between LiDFOB and PECA.…”
Section: Vs Li/limentioning
confidence: 96%
“…The mechanism is that additives are preferably oxidised on the positrode surface to generate a stable interfacial layer, which inhibits the detrimental reaction of electrolytes at high positive potentials. Reported additives include (1) inorganic compounds such as lithium bis(oxalato)borate (LiBOB) [152][153][154][155][156][157][158] and lithium difluoro(oxalato)borate (LiDFOB) 159 , (2) phosphite-derivatives such as trimethyl phosphite (TMP) 160 , tris(hexafluoro-iso-propyl) phosphate (HFiP) 161,162 , tris(trimethylsilyl) phosphite (TMSP) [163][164][165][166] , (Ethoxy) pentafluorocyclotriphosphazene (PFPN), 167 and 1-propylphosphonic acid cyclic anhydride (PACA) 168 , (3) sulfonate esters such as 1,3-propane sultone (PS) 169 , 1,3-propanediol cyclic sulfate (PCS) 170 , and (4) some carboxyl anhydrides 169,171,172 . These additives, some of which are shown wither their molecular structures in Fig.…”
Section: High Voltage Electrolytesmentioning
confidence: 99%
“…It was confirmed that lithium bis(oxalate)borate (LiBOB) or lithium difluoro(oxalato)borate (LiODFB) could work more efficiently as a lithium salt in electrolyte than LiPF 6 to inhibit the Mn 2+ dissolution. Due to the stable film formed on the cathode and anode surfaces in LiBOBbased or LiODFB-based electrolyte, the cycling performance was dramatically improved, especially at high temperature [21][22][23][24][25][26]. However, when mixing with alkyl carbonate solvents, a thick solid electrolyte interface (SEI) layer will be formed in LiBOB-based or LiODFB-based electrolytes, leading to the increase of the interfacial impedance on the negative electrode, and greatly deteriorating the power capability and rate capability of LIB [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to anode, the cathode is also covered by a surface film after cycling in electrolytes, due to reactions with solution components. The electrochemical behavior of cathode material may depend very strongly on its surface chemistry in solutions and phenomena such as surface film formation [25,26,30,31]. Especially, cells with LiBF 2 SO 4 -based electrolyte show stable cycle performance and super rate performance.…”
Section: Introductionmentioning
confidence: 99%